Agroecological living laboratories (all-organic) from Romania "Beleza Store SRL ecological vegetable farm - Valcelele/Călărași" (case study) - Ion Toncea; Tudor Stanciu; Steliana Rodino; Vladimir Adrian Toncea; Gina Fi͏n̂tîneru (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
Since 2005 when, at the initiative of the Finnish Presidency, the European Network of Living Laboratories (ENoLL) was established, the term "living laboratory (LL)" has spread throughout the scientific and technical world because: it aims to stimulate innovation in all its complexity, it can be understood and used according to the particularities of each component of sustainable development - nature, society and economy and in different ways - as a means of stimulating innovation, a multiple approach way, a working methodology, a development strategy, a way to support the transition towards local agri-food sustainability, concept in (re)designing business models, etc. and applied relatively easily, with the help of information and communication technology (ITC), then promising and now fashionable and in full creative momentum in both urban and rural environments. The paper presents the first results of the research project "Living Agroecological Laboratories for the promotion of resilient organic production systems - ALL-Organic", code ERANET-COREORGANIC-ALL-Organic, CORE Organic Cofund financing scheme for the period November 15, 2021 - November 14, 2024, regarding the identification of the specific characteristics of the Agroecological Living Laboratory (ALL-Organic) "SC Beleza Store SRL", corresponding to the structural components of any Agroecological Living Laboratory (ALL): Mission, Activities, Resources, Participants and Context.
Keywords: Q12; 330; living laboratory; agroecology/agroecosystem; field vegetables